Face identity and facial expression representations with adaptation paradigms: New directions for potential applications - Minemoto, Kazusa; Ueda, Yoshiyuki (Frontiers in Psychology, 2022)
Adaptation and aftereffect are well-known procedures for exploring our neural representation of visual stimuli. It has been reported that they occur in face identity, facial expressions, and low-level visual features. This method has two primary advantages. One is to reveal the common or shared process of faces, that is, the overlapped or discrete representation of face identities or facial expressions. The other is to investigate the coding system or theory of face processing that underlies the ability to recognize faces. This study aims to organize recent research to guide the reader into the field of face adaptation and its aftereffect and to suggest possible future expansions in the use of this paradigm. To achieve this, we reviewed the behavioral short-term aftereffect studies on face identity (i.e., who it is) and facial expressions (i.e., what expressions such as happiness and anger are expressed), and summarized their findings about the neural representation of faces. First, we summarize the basic characteristics of face aftereffects compared to simple visual features to clarify that facial aftereffects occur at a different stage and are not inherited or combinations of low-level visual features. Next, we introduce the norm-based coding hypothesis, which is one of the theories used to represent face identity and facial expressions, and adaptation is a commonly used procedure to examine this. Subsequently, we reviewed studies that applied this paradigm to immature or impaired face recognition (i.e., children and individuals with autism spectrum disorder or prosopagnosia) and examined the relationships between their poor recognition performance and representations. Moreover, we reviewed studies dealing with the representation of non-presented faces and social signals conveyed via faces and discussed that the face adaptation paradigm is also appropriate for these types of examinations. Finally, we summarize the research conducted to date and propose a new direction for the face adaptation paradigm.